2013
DOI: 10.1172/jci65665
|View full text |Cite|
|
Sign up to set email alerts
|

A spastic paraplegia mouse model reveals REEP1-dependent ER shaping

Abstract: Axonopathies are a group of clinically diverse disorders characterized by the progressive degeneration of the axons of specific neurons. In hereditary spastic paraplegia (HSP), the axons of cortical motor neurons degenerate and cause a spastic movement disorder. HSP is linked to mutations in several loci known collectively as the spastic paraplegia genes (SPGs). We identified a heterozygous receptor accessory protein 1 (REEP1) exon 2 deletion in a patient suffering from the autosomal dominantly inherited HSP v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
74
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 50 publications
8
74
2
Order By: Relevance
“…Corresponding with the progressive gait disorder, we observed a degeneration of axons within the corticospinal tract at 8 months of age, a finding in line with mouse models of other types of HSP [20][22]. This degeneration mainly affected large diameter axons of the lumbar corticospinal tract.…”
Section: Discussionsupporting
confidence: 85%
“…Corresponding with the progressive gait disorder, we observed a degeneration of axons within the corticospinal tract at 8 months of age, a finding in line with mouse models of other types of HSP [20][22]. This degeneration mainly affected large diameter axons of the lumbar corticospinal tract.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, a REEP1 gene knockout mouse model of HSP was created (Beetz et al, 2013). In situ hybridization analysis of an E18.5 murine sagittal embryo section demonstrated that REEP1 mRNA was only found in neuronal tissues, including cortical brain structures, brainstem, cerebellum, spinal cord, several major ganglia (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A mouse model of REEP1 deletion and a Drosophila model of Rtn2 deletion exhibit characteristics of HSP [77,80]. In general, neurons contain long protrusions, and the integrity of the ER network is more vulnerable to functional impairment.…”
Section: Er Morphology In Multicellular Developmentmentioning
confidence: 99%